A novel engineered strain of Methylorubrum extorquens for methylotrophic production of glycolic acid - Katharina Dietz; Carina Sagstetter; Melanie Speck; Arne Roth; Steffen Klamt; Jonathan Thomas Fabarius (Microbial Cell Factories)
Abstract The conversion of CO2 into methanol depicts one of the most promising emerging renewable routes for the chemical and biotech industry. Under this regard, native methylotrophs have a large potential for converting methanol into value-added products but require targeted engineering approaches to enhance their performances and to widen their product spectrum. Here we use a systems-based approach to analyze and engineer M. extorquens TK 0001 for production of glycolic acid. Application of constraint-based metabolic modeling reveals the great potential of M. extorquens for that purpose, which is not yet described in literature. In particular, a superior theoretical product yield of 1.0 C-molGlycolic acid C-molMethanol −1 is predicted by our model, surpassing theoretical yields of sugar fermentation. Following this approach, we show here that strain engineering is viable and present 1st generation strains producing glycolic acid via a heterologous NADPH-dependent glyoxylate reductase. It was found that lactic acid is a surprising by-product of glycolic acid formation in M. extorquens, most likely due to a surplus of available NADH upon glycolic acid synthesis. Finally, the best performing strain was tested in a fed-batch fermentation producing a mixture of up to total 1.2 g L−1 glycolic acid and lactic acid. Several key performance indicators of our glycolic acid producer strain are superior to state-of-the-art synthetic methylotrophs. The presented results open the door for further strain engineering of the native methylotroph M. extorquens and pave the way to produce two promising biopolymer building blocks from green methanol, i.e., glycolic acid and lactic acid.